THE RELATIONSHIP BETWEEN PARENTAL SUPPORT AND HIGH SCHOOL STUDENTS’ LEARNING MOTIVATION - Nur Lailiah; Ayesha Fayasha Salsabila; Muhammad Roshin Anwar; Arman Kusumadika (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2025)
This study aims to examine the relationship between parental support and students' learning motivation in high schools in Indonesia. This study is a literature review based on local studies that examine the influence of emotional, informational, and instrumental parental support on students' academic motivation. The results show that students who receive adequate parental support tend to have higher self-confidence, persistence, and enthusiasm for learning. Emotional support strengthens students' self-esteem, while informational and instrumental support help build a disciplined and structured learning environment. Therefore, active parental involvement plays a crucial role in improving the learning motivation and academic achievement of high school students in Indonesia.